MANAJEMEN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA ANAK USIA DINI DI BA AISYIYAH BEKU KARANGANOM KLATEN - Muriyanto (STPI Bina Insan Mulia Yogyakarta, 2020)
The purpose of this research is that the writer wants to know how the Management of Learning Islamic Education in Early Childhood at BA Aisyiyah Beku, Karanganom Klaten. In finding the data needed by the author using the method of observation, interviews and methods of documentation. The object of research is the Learning Management of Islamic Religious Education in Early Childhood at BA Aisyiyah Beku, Karanganom, Klaten. After the writer tries to find the data needed, the writer can draw the conclusion that the principal makes the organizational structure in PAUD Bustanul Athfal Aisyiyah Beku Karanganom Klaten, including coaches, advisers, to schools, secretaries, treasurers, administrative staff, educators (teachers) ), Counseling teachers, pediatricians, operators, and administration as well as office boys. All of them work according to their respective duties and sometimes also work together. With a clear division of tasks, the work at PAUD Bustanul Athfal Aisyiyah Beku Karanganom Klaten can be completed at the appointed time and properly. In addition, there are also Islamic religious education materials, including Dawaamul Qur'an, Pearls of the Qur'an, pearls of hadith, daily prayers, daily dhikr, asmaul husna. In addition, the assessment method has been carried out, namely by observation or observation, conversations, assignments, performance, valuation of works, recording of anecdotes, portfolios.